2019
DOI: 10.1161/jaha.119.012008
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Reserve in Fontan Patients: Chronotropic Incompetence or Hemodynamic Limitation?

Abstract: Background Patients with a Fontan circulation achieve lower peak heart rates ( HR ) during exercise. Whether this impaired chronotropic response reflects pathology of the sinoatrial node or is a consequence of altered cardiac hemodynamics is uncertain. We evaluated the adequacy of HR acceleration throughout exercise relative to metabolic demand and cardiac output in patients with a Fontan circulation relative to healthy controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 26 publications
4
52
1
Order By: Relevance
“…In patients with TCPC, the performance strongly relies on cardiovascular balance and pulmonary perfusion rather than ventilation. In these patients, pulmonary blood flow is known to be heart-rate dependent, which in turn depends on autonomic dysfunction, cardiac arrhythmias, and abnormal cardiac filling 47,48 : as expected, our patients with TCPC had chronotropic incompetence and reduced ventricular function.…”
Section: Correlations Between Pft and Cpxsupporting
confidence: 77%
“…In patients with TCPC, the performance strongly relies on cardiovascular balance and pulmonary perfusion rather than ventilation. In these patients, pulmonary blood flow is known to be heart-rate dependent, which in turn depends on autonomic dysfunction, cardiac arrhythmias, and abnormal cardiac filling 47,48 : as expected, our patients with TCPC had chronotropic incompetence and reduced ventricular function.…”
Section: Correlations Between Pft and Cpxsupporting
confidence: 77%
“…35 Recently, cardiac MRI has been used to measure stroke volume and cardiac output during exercise in Fontan patients. 19 An early reduction in stroke volume and a cardiac output plateau at submaximal heart rates were found. We had no direct measurements of central haemodynamics, but our calculation of oxygen pulse at maximal effort supports the concept of impaired stroke volume in the Fontan patients.…”
Section: Discussionmentioning
confidence: 95%
“…It has been suggested that Fontan patients perform better at submaximal exercise level and that training should be designed accordingly. 33 In a recent publication by Claessen et al, 19 they reported Fontan patients with higher increase in heart rate relative to workload than in a control group. However, their control group was not matched regarding age or gender, and the exercise test was only submaximal with heart rates of 144-155 beats per minute, more corresponding to our midpoint values.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations